2007
DOI: 10.1177/0960327106070455
|View full text |Cite
|
Sign up to set email alerts
|

Cell viability and proteomic analysis in cultured neurons exposed to methylmercury

Abstract: Methylmercury is an environmental contaminant with special selectivity for cerebellar granule cells. The aim of this study was to determine the effect of long-term methylmercury exposure on cell viability and cellular proteome in cultured cerebellar granule cells. Primary cultures of mice cerebellar granule cells were treated with 0-300 nM methylmercury at 2 days in vitro (div) and afterwards the cells were harvested at 12 div. 100 nM methylmercury produced loss of cell viability, reduced intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Specific attention should be paid to its organometallic compound, methylmercury, because: i) it has recognized properties as a human neurodevelopmental toxicant (Grandjean and Landrigan, 2006); ii) poisoning incidents with methylmercury have demonstrated the potential of this pollutant as neurotoxicant and its serious health consequences (Castoldi et al, 2008;Ekino et al, 2007;Grandjean et al, 2010;Nakagawa et al, 2002); iii) millions of people are nowadays chronically exposed to this contaminant and there is epidemiological (Marsh et al, 1987; Pinheiro et al, 2007;Yokoo et al, 2003) and experimental (Castoldi et al, 2008;Farina et al, 2009;Vendrell et al, 2007Vendrell et al, , 2010 evidence of the toxic effects of chronic exposure to this metal especially for the nervous system; and iv) previous results from the INMA birth cohort of Valencia (Spain) showed elevated levels of this pollutant in umbilical cord blood, where 70% of newborns had mercury levels above US EPA recommended level, i.e. 5.8 μg/L of MeHg (Ramon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specific attention should be paid to its organometallic compound, methylmercury, because: i) it has recognized properties as a human neurodevelopmental toxicant (Grandjean and Landrigan, 2006); ii) poisoning incidents with methylmercury have demonstrated the potential of this pollutant as neurotoxicant and its serious health consequences (Castoldi et al, 2008;Ekino et al, 2007;Grandjean et al, 2010;Nakagawa et al, 2002); iii) millions of people are nowadays chronically exposed to this contaminant and there is epidemiological (Marsh et al, 1987; Pinheiro et al, 2007;Yokoo et al, 2003) and experimental (Castoldi et al, 2008;Farina et al, 2009;Vendrell et al, 2007Vendrell et al, , 2010 evidence of the toxic effects of chronic exposure to this metal especially for the nervous system; and iv) previous results from the INMA birth cohort of Valencia (Spain) showed elevated levels of this pollutant in umbilical cord blood, where 70% of newborns had mercury levels above US EPA recommended level, i.e. 5.8 μg/L of MeHg (Ramon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MeHg-induced cell death was concentration-and time-dependent, with LC 50 values of 508 ± 199 , 345 ± 47 , and 243 ± 45 nM after exposure for 6, 11, and 16 days in vitro, respectively ( p = 0.05, one-way ANOVA) (Vendrell et al 2010 ) . Contrarily to the effects observed after short term and high concentration (>1 m M) exposure to MeHg, exposure to 100 nM MeHg for 10 days in vitro or to 300 nM MeHg for 5 days in vitro, which did not induce cell death, did not result in inhibition of the glutamate transport nor in changes of intracellular glutamate levels (Vendrell et al 2007(Vendrell et al , 2010Farina et al 2009 ) . All together these results suggest that impairment of neuronal glutamate homeostasis is a key event in the acute-high level toxicity of MeHg, whereas other mechanisms underlie the cellular toxic effects of long-term and low-level exposure to MeHg.…”
Section: Effects Of Methylmercury On Presynaptic Glutamate Transportmentioning
confidence: 96%
“…Prolonged exposure of CGCs to submicromolar concentrations of MeHg also resulted in oxidative stress inducing lipid peroxidation (Fig. 14.2a ) and increasing cell vulnerability against peroxides such as hydrogen peroxide and t-butyl hydroxy peroxide (Vendrell et al 2007 ;Farina et al 2009 ) . The analysis of endogenous regulators of red-ox homeostasis revealed that reduction of GPx activity was the fi rst event induced by prolonged exposure to low MeHg concentration before changes in glutathione (GSH), catalase and glutathione reductase (GR) could be observed (Farina et al 2009 ) .…”
Section: Effect Of Methylmercury On Cellular Red-ox Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent transcriptomic and proteomic analyses revealed a comprehensive set of cellular factors responding to Hg exposure (Hwang et al, 2011;Toyama et al, 2011;Vendrell et al, 2007), it is noteworthy that previous studies have reported the effects of Hg on mRNA and protein syntheses using radiolabeled substrates with brain tissue from regions including the cerebellum, a specific target of Hg (Sarafian and Verity, 1985;Syversen, 1982;Yoshino et al, 1966). These previous reports suggested the hypothesis, which has not been studied recently, that Hg might exert toxicity via modulation of gene expression itself, in addition to altering the profile of gene expression that occurs as a cellular response to Hg.…”
Section: Introductionmentioning
confidence: 99%